Changes in Cortical Thickness Are Associated With Cognitive Ability in Postoperative School-Aged Children With Tetralogy of Fallot - Ma, Siyu; Li, Yaping; Liu, Yuting; Xu, Cheng; Li, Huijun; Yao, Qiong; Wang, Ying; Yang, Zhaocong; Zuo, Pengcheng; Yang, Ming; Mo, Xuming (Frontiers in Neurology, 2020)
In children with tetralogy of Fallot (TOF), there is a risk of brain injury even if intracardiac deformities are corrected. This population follow-up study aimed to identify the correlation between cerebral morphology changes and cognition in postoperative school-aged children with TOF. Resting-state functional magnetic resonance imaging (rs-fMRI) and the Wechsler Intelligence Scale for Children–Chinese revised edition (WISC-CR) were used to assess the difference between children with TOF and healthy children (HCs). Multiple linear regression showed that the TOF group had a lower verbal intelligence quotient (VIQ, 95.000±13.433, p=0.001) than the HC group and that VIQ had significant positive correlations with the cortical thickness of both the left precuneus (p< 0.05) and the right caudal middle frontal gyrus (p<0.05) after adjustment for preoperative SpO2, preoperative systolic blood pressure (SBP), preoperative diastolic blood pressure (DBP) and time of aortic override (AO). Our results suggested that brain injury induced by TOF would exert lasting effects on cortical and cognitive development at least to school age. This study provides direct evidence of the relationship between cortical thickness and VIQ and of the need for strengthened verbal training in school-aged TOF patients after corrective surgery.